TINGKAT BAHAYA EROSI DI SUB DAS TONDANO BAGIAN TIMUR DENGAN APLIKASI SISTEM INFORMASI GEOGRAFI - Irene R.S. Terok; Sandra Pakasi; Joice Supit; Tilda Titah (Universitas Sam Ratulangi, 2015)
ABSTRACTThis study head to analyze the level of erosion (TBE) which occur in the eastern part of watershed Tondano with Geographical Information Systems Applications. The method used in the calculation is the USLE erosion and analysis degree erosion using a table of erosion potential based Geographical Information Systems. Observed variables are rainfall, soil erodibility, length and slope, crop management, soil conservation management. The results showed the level of erosion that occurs in watershed Tondano eastern part is divided into five classes: very heavy (SB), weight (B) moderate (S) light (R), and very light (SR). Very heavy class (SB) with and area of 719.20 hectares or 3.21%. weight (B) with and area of 17.07 hectares or 0.40% for, the class of moderate (S) with an area of 3250.13 or 77.35%. and for the lightweight class (R) with and area of 79.91 hectares or 0.40%. whereas for the classification of very light (SR) with and area of 135.01 hectares or 3.21%.keywords: Rainfall, soil Erodibility, length and Slopes, Crop Management, Land Use.